Spatial-Temporal Patterns and Influencing Factors of Epidemics in Gansu Province During the Qing Dynasty (1644–1911) - Zhao, Haili; Yao, Yamei (International Journal of Social Sciences and Public Administration, 2026)
Understanding the historical dynamics of epidemics is crucial for addressing contemporary global health threats under climate change and globalization. However, most existing studies on historical epidemics in China have focused on eastern coastal regions, while northwestern areas like Gansu-a critical ecological transition zone-remain understudied. Furthermore, comprehensive analyses integrating both natural and social environmental drivers are lacking. To address this research gap, this study investigates the spatial-temporal distribution patterns and influencing factors of plague epidemics in Gansu Province during the Qing Dynasty (1644–1911) using historical records, spatial autocorrelation analysis, and geographic detectors. Results reveal that plague frequency peaked during the Tongzhi era (1863–1874), with epidemic coverage and affected counties reaching maxima in 1724 and 1769, respectively, predominantly occurring in summer and autumn. Spatially, plague spread evolved from fragmented distributions in the early period to increasingly clustered and contiguous patterns in central and eastern Gansu. The epidemics were driven by the interplay of natural and social factors, with the interaction between transportation route length and elevation exhibiting the strongest synergistic effect. These findings provide historical insights for understanding regional epidemic dynamics and inform contemporary public health strategies in ecologically vulnerable regions.